2005
DOI: 10.1002/prot.20424
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of two insect‐specific spider toxins and their pharmacological interaction with the insect voltage‐gated Na+ channel

Abstract: Delta-paluIT1 and delta-paluIT2 are toxins purified from the venom of the spider Paracoelotes luctuosus. Similar in sequence to mu-agatoxins from Agelenopsis aperta, their pharmacological target is the voltage-gated insect sodium channel, of which they alter the inactivation properties in a way similar to alpha-scorpion toxins, but they bind on site 4 in a way similar to beta-scorpion toxins. We determined the solution structure of the two toxins by use of two-dimensional nuclear magnetic resonance (NMR) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…It has been observed in sodium channel neurotoxins from spiders and scorpions that C-terminus amidated peptides have stronger affinity for their sodium channel receptors [9,24]; that is, the exchange of an anionic charge for a neutral one at the C-terminus increases the overall positive charge of amidated peptides which is correlated with their receptor affinities [31].…”
Section: Biological Activitymentioning
confidence: 99%
“…It has been observed in sodium channel neurotoxins from spiders and scorpions that C-terminus amidated peptides have stronger affinity for their sodium channel receptors [9,24]; that is, the exchange of an anionic charge for a neutral one at the C-terminus increases the overall positive charge of amidated peptides which is correlated with their receptor affinities [31].…”
Section: Biological Activitymentioning
confidence: 99%
“…Using the isolated cockroach axon preparation and cloned para/tipE insect Nav channels expressed in Xenopus oocytes they have been shown to slow insect Nav channel inactivation, with no shift in the voltage dependence of activation. They also have no effect on Nav1.2/β1 channels at concentrations up to 10 µM (Ferrat et al, 2005). This action is similar to site 3 neurotoxins such as…”
Section: Jingzhaotoxin Imentioning
confidence: 58%
“…antagonize channel inactivation. However, profound differences between ␦-Palu-IT1 and -2 and scorpion ␣-toxins were noted, the former competing with scorpion ␤-toxins for binding to receptor site 4 and not influencing the kinetics of channel inactivation (23,53). It was therefore suggested that ␦-Palu-IT1 and -2 only macroscopically resemble typical scorpion ␣-toxins but, unlike them, influence the inactivated-to-closed state transition process (53).…”
Section: Discussionmentioning
confidence: 99%
“…Apart for overall sequence similarity, all of these toxins (except for ␦-Palu-IT3) are C-terminally amidated and contain eight strictly conserved halfcystine residues that most probably account for a presumably common molecular fold. To date, spatial structures of -Aga-1 and ␦-palutoxins-IT1 and -2 are known, all showing a high degree of similarity (53,54) and conforming to the inhibitor cystine knot (ICK) motif most common for spider venom neurotoxins (4,55). Even in the absence of experimental data proving the exact disulfide connectivity, it is therefore not unreasonable to surmise the typical ICK motif for the ␤/␦-agatoxins.…”
Section: Discussionmentioning
confidence: 99%